Implementation of Organizational Psychology Theory in The Dynamics of Social Organization in Madrasah - Nurlaela, Lala; Wardany , Diny Kristianty; Pahlawani , Kania Agustina (Al-Ilmu, 2025)
Madrasahs, as Islamic educational institutions, face complexities in managing their organizations, as they must combine religious values ​​with the demands of modern management. The social dynamics that emerge within them require a deep understanding of organizational psychology theory to create an effective, harmonious work environment that aligns with Islamic identity. This study aims to analyze the implementation of organizational psychology theory in the social dynamics of madrasahs, identify factors that influence organizational effectiveness, and formulate a practical model that suits the characteristics of madrasahs. The method used is a qualitative approach with a case study of three Madrasah Tsanawiyah (Islamic junior high) schools in Sukahaji District, Majalengka. Data were obtained through in-depth interviews with 45 informants, participant observation, and analysis of organizational documents. The results show that the application of Herzberg's motivation theory with the addition of a spiritual dimension, transformational leadership based on Islamic role models, and brotherhood-based communication have a positive impact on the organizational climate. The unique culture of madrasahs is an important mediator in the application of these theories. This study produces the Islamic Organizational Psychology Model (IOPM) which includes three layers: foundation, adaptation, and implementation. In conclusion, adapting organizational psychology theory to Islamic values ​​can increase the effectiveness of madrasas while maintaining Islamic identity.